An Ethnosemantic Study of Palu Toponym and Its Association with Natural Hazards - Syamsuddin Syamsuddin; Rizky Anugrah Putra; Annisah Wulansari (Journal of English Language Teaching and Linguistics, 2023)
This research investigates how the naming of locations in Palu, Central Sulawesi, Indonesia describes the geographical and social conditions in the local area. After the earthquake and tsunami on September 28 2018, in Palu, considerable geographical studies have desired to discover the causality of this catastrophic natural phenomenon. Nevertheless, behind it all, the Kaili tribe, an indigenous tribe on the mainland of Central Sulawesi, believes that several areas in Palu are unfit for habitation because of the history of natural events that have occurred. They sketch this information using toponymy that modern society has often ignored. Moreover, acculturation and globalization have made people overlook local culture and history. The present study operated a different perspective to reveal that the toponymic naming in the Palu area. Those toponyms are derived from the Kaili language reflecting geographical conditions, history and vegetation. The researcher discovered that based on ethnolinguistic fact, several zones were the hotspots of the worst earthquakes and liquefactions and reflected in several toponyms that today's society has forgotten. Using ethnosemantics tracing, historical, and geographical observation and involving cultural and indigenous figures, the researcher answered this phenomenon based on evidence. The implications and results of the findings of this study will be discussed further in the discussion section.